Pembangunan Sistem Informasi Geografis Potensi Desa Berbasis Web BPS Kota Madiun - Rizka Indah Pristania; Nori Wilantika (Politeknik Statistika STIS, 2022)
Potential Villages are a source of data bases on territories owned up to the village level. Potential Villages data can be obtained from Potential Villages Data Collection conducted by the Badan Pusat Statistik (BPS) in three censuses in a period of ten years. The results of the Potential Villages Data Collection are presented in the form of publications. These publications can be re-managed and can be developed for the benefit of the village. To obtain an overview of publication information, it is necessary to manage and present it properly through attractive data visualization. This is because Potential Villages data is still presented in the form of tables, graphs, brief descriptions and static area maps as well as publications in print media that need to change the file format to Excel or CSV for further data analysis. Potential Villages data on publication is not yet interactive and dynamic. Communication that runs only in one direction, namely the publisher of publications to data users. Based on these problems, the researcher proposes a solution in the form of building a geographic information system using web-based Potential Villages data. So that the system can present data in the form of data visualizations in the form of interactive maps and dynamic data tables that can be downloaded directly, both maps in PNG format and data tables in Excel, CSV and PDF formats and can copy tables and print tables. Researchers in building this system use the System Development Life Cycle Waterfall Model (SDLC Waterfall Model). Testing for this system uses the Black Box Testing method and for system evaluation using the System Usability Scale (SUS). The evaluation results show that the system built produces an overall average score of 87.92, which indicates the system is feasible and in accordance with user needs.